Chelation enables selectivity control in enantioconvergent Suzuki–Miyaura cross-couplings on acyclic allylic systems - Stojalnikova, V; Webster, SJ; Liu, K; Fletcher, SP (Nature Research, 2024)
Asymmetric Suzuki–Miyaura cross-couplings with aryl boronic acids and allylic electrophiles are a powerful method to convert racemic mixtures into enantioenriched products. Currently, enantioconvergent allylic arylations are limited to substrates that are symmetrical about the allylic unit, and the absence of strategies to control regio-, E/Z- and enantioselectivity in acyclic allylic systems is a major restriction. Here, using a system capable of either conjugate addition or allylic arylation, we have discovered the structural features and experimental conditions that allow an acyclic system to undergo chemo- and regioselective, enantioconvergent allylic Suzuki–Miyaura-type arylation. A wide variety of boronic acid coupling partners can be used, and both alkyl and aromatic substituents are tolerated on the allylic unit so that a wide variety of structures can be obtained. Preliminary mechanistic studies reveal that the chelating ability of the ester group is crucial to obtaining high regio- and enantioselectivity. Using this method, we were able to synthesize the natural products (S)-curcumene and (S)-4,7-dimethyl-1-tetralone and the clinically used antidepressant sertraline (Zoloft).